Analisis Pengaruh Retribusi Daerah Terhadap Pendapatan Asli Daerah Kabupaten Lombok Utara - Shinta Eka Kartika; Sutianingsih Sutianingsih; Widowati Widowati (Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to determine the level of growth, effectiveness, contribution, and prediction of revenue (PAD) in North Lombok Regency. The data collection technique uses documentation, namely data on regional retribution and PAD for the years 2014-2019. Data analysis using descriptive analysis. The results show that the growth of regional retribution has increased in 2014 and 2015 by 76.3 percent and 72 percent, respectively. Meanwhile, in 2016-2019, the realization of regional retribution decreased by 56.4 percent, 9 percent, 4.7 percent and 55.3 percent respectively. The level of effectiveness of the collection of regional retribution in 2014 was 114.4 percent (very effective). Meanwhile, in 2015 and 2016, respectively 89.1 percent and 88.2 percent (less effective). And in 2017, 2018 and 2019 respectively 66.9 percent, 74 percent and 39.9 percent or included in the ineffective category. The contribution of regional retribution to PAD in 2014-2019 was 16.82 percent (not good), 22.83 percent (good enough), 7.88 percent, 6.16 percent, 6.76 percent and 2.69 percent respectively (not very good). The prediction of regional retribution for 2020-2022 is obtained by an average revenue for three years, namely IDR 19,474,844,122 or there will be an average increase of 33 percent per year. Meanwhile, the PAD prediction obtained an average revenue of IDR 342,948,257,802 or there will be an average increase of 33 percent per year.